1988
DOI: 10.1123/ijsb.4.1.68
|View full text |Cite
|
Sign up to set email alerts
|

The Snatch Technique of World Class Weightlifters at the 1985 World Championships

Abstract: The purpose of this study was (a) to describe the snatch technique in terms of kinematic and external and internal kinetic parameters, and (b) to compare the results for athletes of different groups and weight categories. By means of three-dimensional film analysis and measurements of ground reaction forces during the 1985 World Championships in Sweden, it was possible to analyze the spatial movements and to calculate joint moments of force in each leg. Concerning the kinematics, a snatch technique starting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 1 publication
6
93
2
12
Order By: Relevance
“…In light of the results for the H-M group, this indicates that in spite of the moderate-to-high ground reaction force, the stimulus for beneficial geometric adaptation seems to be diminished by the lower rate of loading. Differing from power-lifting (squat, bench press, and deadlift), weightlifting movements such as the snatch, clean, and jerk are explosive and involve more impact: peak vertical ground reaction forces are 2.5-4 times BW and estimated impact loading rates vary from about 10-50 BWs -1 [53][54][55][56]. This warrants further investigation of femoral neck strength among weightlifters.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In light of the results for the H-M group, this indicates that in spite of the moderate-to-high ground reaction force, the stimulus for beneficial geometric adaptation seems to be diminished by the lower rate of loading. Differing from power-lifting (squat, bench press, and deadlift), weightlifting movements such as the snatch, clean, and jerk are explosive and involve more impact: peak vertical ground reaction forces are 2.5-4 times BW and estimated impact loading rates vary from about 10-50 BWs -1 [53][54][55][56]. This warrants further investigation of femoral neck strength among weightlifters.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Thus, after maximum power applied to the bar was estimated by using a simple method where the barbell weight was multiplied by Vmax (Hori et al, 2006), the WC group was found to output 35% higher maximum power per unit body weight (31.3Ϯ3.5 W/kg) than the JP group (23.1Ϯ3.0 W/kg) (pϽ0.05). Since the lifted weights in weightlifting correlated highly with the lean body mass (Okada & Funato, 1993), those findings may be attributed mainly to differences in capability to exert force and power such as muscle volume, its distribution, and muscle strength per muscular crosssectional area.During the snatch, it may be suggested that the moment of the hip joint corresponds to 2-4 times that of the knee joint and load on the hip joint is increased with increasing barbell weight (Baumann, 1988). Therefore, the extension movement of the hip joint is positioned as the most contributing joint movement during the snatch.…”
mentioning
confidence: 99%
“…Alongside with it searching of more effective trajectories (the most wide spread among weight-lifters) is remaining the permanent subject of their discussions. In some works trajectory (А) [16] is offered; in other -trajectory of B type [14,25]. In his turn Hiskia G. [18] came to conclusion that type C is the most wide-spread.…”
mentioning
confidence: 99%